The perpetration of on- and offline hate speech among secondary school students - Cáceres, Juan Manuel Bellido; Martínez, Pilar Rodríguez; Espinosa, Joaquín Jaime Sánchez; Joya, Lucía Martínez (Frontiers in Human Dynamics, 2025)
This study analyses the relationships between witnessing and perpetrating hate speech, both on- and offline. It is based on data extracted from a purpose-designed questionnaire answered by a total of 571 secondary school students in Almería. We used SPSS software to analyse the data collected, employing statistical analysis techniques that included binary logistic regression, and chi-square and omnibus tests of model coefficients to determine consistency. The relationships between hate speech in both environments point to an escalation of violence and transference between online and in-person aggressions. Also evident is the influence of close social environments, such as violence in schools. When a student suffers hate speech in either environment, the likelihood of them going on to perpetrate hate speech increases significantly. We conclude that the perpetration of hate speech, both on- and offline, is explained by students having witnessed or suffered in-person hate speech; having seen or heard hate speech online; and, above all, having suffered hate speech online.